Sistem Pendukung Keputusan Kelayakan Pemberian Pinjaman dengan Metode Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) - Kecitaan Harefa (Jurnal Informatika Universitas Pamulang, 2020)
Cipta Harapan Jaya Cooperative Savings and Loans is a financial institution that provides loan funds to the community, namely micro, small and medium entrepreneurs. Lending is done with a system and procedure that is easy, fast and safe. But many customers do not fulfill their obligations or are not fluent in paying installments, thereby causing bad credit and reducing cooperative income. The cause of customers who are not fluent in paying installments cannot be detected with the current selection system for prospective customers. This research proposes the use of a decision support system with the Analytical Hierarchy Process (AHP) method used to determine the criteria weights and the Simple Additive Weighting (SAW) method to find the best alternative. Both of these methods can facilitate the cooperative in making decisions about prospective customers who apply for loans more effectively and efficiently. The criteria used are collateral, capital, condition, capacity, and character. Based on the results of the calculation and implementation of the proposed method obtained an accuracy of 90.67%. This means that this accuracy is close to good value and can be used as a guideline for determining potential customers who are eligible for loans.